Technique of agrotechnical field experiment - V. V. Golubev; A. V. Kudryavtsev; A. S. Firsov; M. A. Safonov (Сельскохозяйственные машины и технологии)
Application of modern technologies and innovative technical equipment at cultivation of grain-crops, including winter wheat, flax, clover and rape, causes actuality of carrying out the multivariable field test. The planned long-term field experience of determination of dependence of the productivity of the cultivated agricultural cultures on the set factors will allow to justify basic technological methods and confirm optimal parameters and modes of operations of innovative working tools for tillage, sowing and crop protection. By results of planning of field experiment width and length of a plot were 3 and 20 m respectively. At randomized placement for one crop cultivation 81 registration plots were necessary. The general size of the test field at a research of three factors with three levels of variation was 110 m width and 215 m length. Before conducting field experiment the authors fixed an initial condition of a soil profile, agronomical and biological characteristics of the soil. Change of soil properties of the and also crops vegetation was noted at of the end of carrying out studies of each series of tests. The main response of field experiment conducting was the productivity. On the basis of the received results more than 27 hectares will be cultivated to increase crop productivity by 17-19 percent owing to the saved-up soil fertility and introduction of innovative technological and technical means of cultivation. The developed recommendations will be realized at agricultural enterprises in the Tver’ region and in others regions of the of the Non-black earth zone.